Soldadura fuerte del compósito TiC/Ni a la superaleación Inconel 600 - Braulio Sánchez, Mariano (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The metal matrix composite materials (MCMM) are considered among the most promising materials for advanced applications. The possibility of joining by brazing (joining brazing) TiC/Ni composite to a nickel-base superalloy, is a major challenge in the study and integration of MCMM's in structural applications and high temperature performance. This paper studies the effect of time and temperature on the microstructure work and bond strength composite TiC/Ni (60 vol.% TiC) a superalloy Inconel-600 (74Ni, 16Cr, 10FE), using as filler BNI3 AWS alloy foil (92.3Ni, 3.2B, 4.5Si, 0.06 C) of 70 microns thick. The research concurs in the research cultivated in Composite Materials Laboratory of IIM-UMSNH on the synthesis and characterization of metal matrix composite materials with functional and high temperature structural applications; in this case, brazing of a TiC/Ni composite to Inconel-600.

Los materiales compósitos de matriz metálica (MCMM) están considerados entre los materiales más promisorios para aplicaciones avanzadas. La posibilidad de unir por soldadura fuerte (unión brazing) el compósito TiC/Ni a una superaleación base níquel, constituye un reto importante en el estudio e integración de los MCMM’s en aplicaciones estructurales y comportamiento a alta temperatura. El presente trabajo estudia el efecto del tiempo y la temperatura de trabajo en la microestructura y resistencia de la unión compósito TiC/Ni (60 vol.% TiC) a superaleación Inconel-600 (74Ni, 16Cr, 10Fe), empleando como material de aporte laminilla de aleación AWS BNi3 (92.3Ni, 3.2B, 4.5Si, 0.06 C) de 70 μm de espesor. La investigación concurre en la línea de investigación cultivada en el Laboratorio de Materiales Compuestos del IIM-UMSNH relativa a la síntesis y caracterización de materiales compósitos de matriz metálica con aplicaciones funcionales y estructurales a alta temperatura; en este caso, soldadura fuerte de un compósito TiC/Ni a Inconel-600.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2012-0123; Soldadura; Compósito; Inconel 600; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5167